Socio-cultural dimensions of reproductive health among selected Mandaya women in Davao Oriental - Santos, Julie Ann Ariate (Animo Repository, 1995)
Studies on reproductive health among women in tribal groups have not been given the attention that it deserves.This study aimed to look at the socio-cultural dimensions which affect the reproductive health of the selected Mandaya women in Davao Oriental.Purposive sampling was utilized in selecting the fifty Mandaya women from three different areas of Davao Oriental.Interview schedule was used in gathering pertinent data. Descriptive statistic was employed using the frequency, mean and median.Results of the study showed that the Mandaya women tended to marry quite early, thereby increasing the chances of their having more babies. With the increase of pregnancy was the threat of complications which contributed to the maternal morbidity of the women. Education have no bearing where traditional practices are concerned. The study revealed that even women who have gone to school tended to cling to the beliefs and practices handed down from generation to generation. Syncretism was the mode of practice used by the Mandaya women when it came to their health. Modern technology were availed of but the traditional practices were also carried side by side. Ethnographic studies should be encouraged because the culture of a tribal group is very rich and very informative. Focus should be made towards their health because it is often the most neglected area of their lives and many of the women and including the children face greater risk in their health. Program interventions should be made based on the needs of the people and not on the desires of program planners alone. It should be done in a way that the cultural beliefs and practices will be intact. Harmful practices should be analyzed thoroughly before an action will be made. Ethical issued should be addressed properly so as not to offend the ethnic communities, as well as, to respect that which is theirs alone.